A situação atual dos Tapirapê - Oliveira, Roberto Cardoso de (Museu Paraense Emílio Goeldi, 2023)
The text presents information about the history of the Tapirapé, including the drastic reduction in the number of Indians due to conflicts with other groups and diseases brought by the colonizers. The Tapirapé live in a single village and face challenges such as lack of resources and pressure from non-indigenous society. The document also discusses initiatives to preserve the culture and customs of the Tapirapé, as well as the importance of respecting and valuing the cultural diversity of indigenous peoples.